2010
DOI: 10.1371/journal.pone.0009659
|View full text |Cite
|
Sign up to set email alerts
|

Immune Requirements of Post-Exposure Immunization with Modified Vaccinia Ankara of Lethally Infected Mice

Abstract: Current prophylactic vaccines work via the induction of B and T cell mediated memory that effectively control further replication of the pathogen after entry. In the case of therapeutic or post-exposure vaccinations the situation is far more complex, because the pathogen has time to establish itself in the host, start producing immune-inhibitory molecules and spread into distant organs. So far it is unclear which immune parameters have to be activated in order to thwart an existing lethal infection. Using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Only one study has directly compared differences between failed post-exposure vaccination protection (MVA-intranasal) and successful post-exposure vaccination protection (MVA-intravenous) in the ECTV model. Results of that study indicate that activation of innate and adaptive immunity shown by increased cytokine and neutralizing antibody production as well as activation of NK and T cells is important for post-exposure vaccination protection [52]. However, a more recent study in the ECTV model indicates that B cells, but not T cells, are dispensable in protecting animals vaccinated with MVA (intranasal) and then challenged 2 days later with a 3× LD 50 dose of ECTV [85].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only one study has directly compared differences between failed post-exposure vaccination protection (MVA-intranasal) and successful post-exposure vaccination protection (MVA-intravenous) in the ECTV model. Results of that study indicate that activation of innate and adaptive immunity shown by increased cytokine and neutralizing antibody production as well as activation of NK and T cells is important for post-exposure vaccination protection [52]. However, a more recent study in the ECTV model indicates that B cells, but not T cells, are dispensable in protecting animals vaccinated with MVA (intranasal) and then challenged 2 days later with a 3× LD 50 dose of ECTV [85].…”
Section: Discussionmentioning
confidence: 99%
“…Mice that are incapable of producing poxvirus specific IgG and IgM are not protected by post-exposure MVA vaccination (intravenous) at day 3 post-exposure whereas wild type mice are which indicates the importance of neutralizing antibodies [52]. The time it takes a virus to spread to the point where post-exposure vaccination is not beneficial will depend in part on the incubation period of the virus and the kinetics of the immune response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…injection of MVA induces strong systemic cytokine responses and DC activation35, 59 and induces stronger CD8 T‐cell responses than immunization via peripheral routes (see ref. 59 and HL, unpublished observation), we speculate that systemic delivery of MVA renders it more immunogenic. This is in line with enhanced therapeutic anti‐tumour effects after i.v.…”
Section: Discussionmentioning
confidence: 99%